Effect of (EMS) Exercises on Some Physical Indicators and Body Measurements of Women Aged (30-45) Years (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the study focused on the use of electrical muscle stimulation technology and the interestin physical and health fitness. Where the researchers noted, through their presence in the gyms for fitnessand ideal weight loss, of several determinants that reduce the possibility of practicing sports activities thatcontribute to maintaining their agility and aesthetics and not accumulating fat in their body, and some ofthem resort to the use of fat oxidizing drugs that have many drawbacks, which reflects negatively on publichealth and aesthetics, therefore, the two researchers decided to prepare special exercises using (EMS)technology according to standardized scientific foundations aimed at the side of electrical stimulation ofthe muscles, which gives high excitement, which helps to complete physical exercises and access to weightloss and improve appearance in a fast and effective way, and the goal of the research is to prepare specialexercises using (EMS) on some physical indicators and body measurements for women aged (30-45) years,the researchers used the experimental approach by pre and post testing for the experimental and controlgroups, and the research community was identified as trainees in the Student Club in the Sports ActivityHall / University of Baghdad, for the training season 0 202, whose number was (18) trainees, as the researchsample was chosen by the method of comprehensive enumeration and the sample was divided into twoexperimental groups. And the control group, with (9) trainees for each group, physical effort was appliedusing EMS technology on the experimental group for a period of eight weeks, with three training units perweek, and they used the SPSS statistical bag to process the data and obtain the results. (30-45) years old.